2020
DOI: 10.1074/jbc.ra119.012495
|View full text |Cite
|
Sign up to set email alerts
|

The USP14–NLRC5 pathway inhibits titanium particle–induced osteolysis in mice by suppressing NF-κB and PI3K/AKT activities

Abstract: Total hip arthroplasty (THA) is a widely-used surgical intervention for treating patients with end-stage degenerative and inflammatory osteoarthropathy. However, wear particles from the artificial titanium joint can induce osteolysis, limiting the long-term survivorship of THA. Monocyte/macrophage lineage cells are the key players in the response to wear particles, and the proinflammatory NF-κB and phosphoinositide 3-kinase (PI3K)–AKT Ser/Thr kinase (AKT)-signaling pathways have been shown to be the most impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…To elucidate the mechanism by which ATRAP interacts with and stabilizes PBX3 protein, we conducted co-immunoprecipitation assays followed by mass spectrometry to screen ATRAP-interacting proteins. Mass spectrometry data ( Table S5 ) indicated that the USP14, one of three proteasome-related deubiquitinating enzymes that can remove ubiquitin from the proteasome substrate before it is degraded 32 , was a strong candidate for further binding validation (Figure 4 J). We subsequently performed co-IP assays with a Flag-tagged ATRAP or USP14 antibody to validate whether ATRAP interacts with endogenous USP14.…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the mechanism by which ATRAP interacts with and stabilizes PBX3 protein, we conducted co-immunoprecipitation assays followed by mass spectrometry to screen ATRAP-interacting proteins. Mass spectrometry data ( Table S5 ) indicated that the USP14, one of three proteasome-related deubiquitinating enzymes that can remove ubiquitin from the proteasome substrate before it is degraded 32 , was a strong candidate for further binding validation (Figure 4 J). We subsequently performed co-IP assays with a Flag-tagged ATRAP or USP14 antibody to validate whether ATRAP interacts with endogenous USP14.…”
Section: Resultsmentioning
confidence: 99%
“…Wear particles can be sensed by macrophages either in the free stage or when bound to carrier proteins. Receptors on the macrophage membrane [pattern-recognition receptors (PRRs)] or intracellular receptors [nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs)], when wear particles are phagocytosed, can be activated to deliver inflammatory signals, which is elucidated in our previous research studies. , Intracellular pathways, such as NF-κB and IRF3 and macrophages M1 polarization, are subsequently activated to initiate inflammatory responses. , In recent studies, TBK1, a member of unconventional IKK family, has been proved to be dimerized by STING, and the activation of TBK1 could further activate the NF-κB pathway by phosphorylating IκB proteins for degradation. Therefore, we hypothesized that STING-modulated TBK1 may regulate TiPs-induced osteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments of immunofluorescent staining and confocal microscopy were performed essentially as described in Fang et al [ 44 ]. Shortly, macrophages were seeded in confocal dishes fixed with 4% paraformaldehyde after different treatments.…”
Section: Methodsmentioning
confidence: 99%